SURFACE URBAN COOL ISLAND ASSESSMENT IN VILLAGE-LEVEL TOURISM DESTINATIONS USING GIS AND PRINCIPAL COMPONENT ANALYSIS - Hernina, Revi; Wicaksono, Arif (Jurnal Geografi Lingkungan Tropik (Journal of Geography of Tropical Environments), 2024)
This study describes the process to generate classification of village-level tourism destinations known as kampung tematik in Bogor Municipality based on values from Surface Urban Cool Island (SUCI), Urban Index (UI) < -0.2, Normalized Difference Vegetation Index (NDVI) >0.3, and Normalized Difference Built-up Index (NDBI) < 0. SUCI values represent the cool temperature which usually associated with heavy greenery and dense vegetation, while UI < - 0.2, NDVI > 0.3, and NDBI < 0 are associated with dense and healthy vegetation. Herein, Band 10 from Landsat 8 was processed to derive land surface temperature (LST) and further, SUCI image was derived from LST image by employing SUCI algorithm. All three variables namely NDVI, NDBI, and UI were also processed from Landsat 8 dated to 24 May 2020. These four images of SUCI, NDVI, NDBI, and UI were superimposed with 39 kampung tematik locations which resulted in 14 locations having non-zero values. The values from four variables in 14 locations were inputted into Principal component Analysis (PCA) using R software version 4.1.3. PCA result shows there are four groups of locations based on variables representing cool island and dense vegetation namely, locations with area percentage of SUCI < 10% (Group 1), low values in three variables (Group 2), high values in two variables (Group 3), and high values in three variables (Group 4).